Genetic parameters for longevity traits in UK dairy goats - Geddes, L.; Desire, S.; Mucha, S.; Coffey, M.; Mrode, Raphael A.; Conington, J. (2018)
Genomic selection on UK dairy goats began in 2015. New traits for selection have evolved since that time with the addition of new genotypes for the reference population. The objectives of this study were to define longevity in terms of lifespan and production, to estimate their heritabilities, and calculate phenotypic and genetic correlations. The dataset comprised records on 12,233 female dairy goats based on two genetically linked farm sites. The pedigree contained information on 40,422 individuals. Heritabilities of the longevity traits were found to range from 0.08 to 0.46, with moderate to high phenotypic and genetic correlations between the lifetime longevity and production longevity traits. The results will allow genetic improvement in dairy goats by incorporating longevity into a breeding index with production, health and maintenance traits. The next step following this work is to produce genomic breeding values for longevity traits that will allow genomic selection for use in UK dairy goat breeding programmes.